Visual Identity Velocity Burger & Coffee Kota Padang - Kevin Hasbi Apriarto; San Ahdi (Universitas Katolik Widya Karya Malang, 2023)
This design is designed in such a way as to produce an alternative media for consumers from Velocity Burger & Coffee to know more about the products being sold and what merchandise is provided by Velocity Burger & Coffee. The problem identified is the number of visitors or customers who do not know what products they sell, and what facilities are provided by Velocity Burger & Coffee. To find a way out of the above problems, the SWOT analysis method is used which stands for strengths, weaknesses, opportunities, threats. This method begins with finding and understanding the problems experienced based on data, then proceed with designing the media from the results of previous data analysis, then developing or designing from the initial design, and the final design results are disseminated through several digital platforms or print outs. This design will produce an output, namely media posters, roll up banners as media to convey information regarding products and merchandise sold by Velocity Burger & Coffee. Making media posters and roll up banners has proven effective in increasing awareness and attracting people to buy food and beverage products from Velocity Burger & Coffee. This is evident from the fact that the message conveyed in the poster media is easily understood by the target audience. And besides designing the main media, several supporting media were also designed, such as: Posters, Roll Up Banners, Social Media, Totebags, Accessories, T-shirts, Lighters, and Stickers.